Study on Lubrication Characteristic of Rubber Bearing based on Viscoelasticity and Vibrative Load - Yabo Zhou; Youqiang Wang; Cong Wei; Shenwen Long (Jixie chuandong)
Based on the viscoelasticity of rubber bearing material, an infinite line contact bearing lubrication model with transient effects is established. Based on three-parameter solid creep model and coupled vibration load, the elastohydrodynamic lubrication analysis of rubber bearings is carried out. The maximum pressure and minimum film thickness of the rubber bearing lubricant film under three load vibration situations are calculated and analyzed, compared with the case that the creep effect is not considered. The changes of lubrication film pressure and film thickness of rubber bearing under the same load and different time are discussed. The multigrid method is adopted to solve the pressure, Newton iteration is adopted to solve the bottom layer and multigrid integral method is adopted to solve the elastic deformation in order to improve the convergence accuracy. The results show that when the viscoelasticity of the rubber bearing is taken into account, the pressure of the lubricant film vibrates in the same form as the load vibration. The pressure will reach a larger value at the beginning of the creep and the whole pressure profile declines to stability with the running time increases. The thickness of the lubricant film vibrates in the opposite form with the load vibration. The film thickness will take a smaller value at the beginning, the overall increases and tends to be stable with the running time increases. The supporting region becomes larger over time under the same load, the pressure profile of the lubricant film decreases and the film thickness becomes thicker.